Bioelectric properties of cystic fibrosis airways obtained at heart-lung transplantation. Issue 12 (December 1992) - Alton, E W; Rogers, D F; Logan-Sinclair, R; Yacoub, M; Barnes, P J; Geddes, D M
Abstract : BACKGROUND: The basic defect in cystic fibrosis centres on abnormal ion transport in affected tissues such as the respiratory tract. Heart-lung transplantation provides a limited supply of native lower airways from these patients. The feasibility of in vitro studies of bioelectric properties and ion fluxes in lower airways, obtained at heart-lung transplantation from patients with cystic fibrosis, has been assessed. Comparison was made with airways from patients without cystic fibrosis. METHODS AND RESULTS: Tissue segments were mounted in Ussing chambers under open circuit conditions. The basal potential difference in tissues from nine patients with cystic fibrosis was -3.6 mV (SE 0.3 mV), not different from tissues from 12 patients without cystic fibrosis of -3.6 mV (0.5 mV). Amiloride (10 microM) caused a significantly greater fall in potential difference in bronchi from patients with cystic fibrosis (83.5% (SE 2.9%)) than in those from controls (55.1% (7.1%)). Isoprenaline (100 microM) produced no significant change in bioelectric properties in non-cystic fibrosis tissues, but induced a 26.2% (6.3%) increase in potential difference in cystic fibrosis airways. The latter response was reduced by amiloride pretreatment. Mucosal chloride substituted Krebs-Henseleit solution caused no change in bioelectric properties in cystic fibrosis airways. Sodium substituted Krebs solution produced a substantial fall in potential difference similar in magnitude to that seen after amiloride. Isotropic flux measurements showed no significant differences between non-cystic fibrosis and cystic fibrosis airways. No net movement of Na+ or Cl- was detected under open circuit conditions in either group. CONCLUSIONS: Cystic fibrosis bronchi obtained at heart-lung transplantation provide a viable source of tissue for in vitro studies of bioelectric properties. The increased response to amiloride characteristic of the upper airways in cystic fibrosis is retained in these tissues, as is the reduced chloride conductance. Although no differences in isotopic fluxes were seen between non-cystic fibrosis and cystic fibrosis tissues, heavily infected airways from patients with cystic fibrosis may not be suitable for ion flux measurements.